Autophagy and Cathepsin D mediated apoptosis contributing to ovarian follicular atresia in the Nile tilapia. Issue 11 (29th July 2019) - Sales, Camila Ferreira; Melo, Rafael Magno Costa; Pinheiro, Ana Paula Barbosa; Luz, Ronald Kennedy; Bazzoli, Nilo; Rizzo, Elizete
Abstract: Follicular atresia is a hormonally controlled degenerative process involving apoptosis of the somatic and germ cells. Since different signaling pathways can induce cell death, the aim of the present study was to investigate cell death signaling and crosstalk between autophagic, apoptotic, and lysosomal proteins during follicular atresia in Nile tilapia. For this, females were kept in controlled conditions for 21 days, and ovary samples were collected weekly. The atretic follicles (AF) were analyzed in three regression phases: Early, advanced, and late. Under electron microscopy, the follicular cells exhibited numerous protein synthesis organelles in the early AF. Immunoreactivity for Bcl2, Beclin1, Lc3, and Cathepsin D increased significantly in advanced AF ( p < .001), when follicular cells were in intense yolk phagocytosis. In this phase, autophagosomes and autolysosomes were frequently observed. In the late AF, follicular cells had a markedly electron‐lucid cytoplasm and immunoreactivity for Bax and TUNEL assay indicated an elevated apoptosis rate. Colocalisation of Lamp1/Cathepsin D and Lc3/Caspase‐3 suggests dynamic crosstalk between the autophagy, apoptosis, and lysosome pathways. Taken together, the data indicate that autophagy plays a role in the homeostasis and clearance of the follicular cells preceding Cathepsin D mediated apoptosis during follicular atresia in Nile tilapia. Abstract : Taken together, our data support that autophagy is essential to maintain follicular cell viability during yolk phagocytosis in the advanced phase of follicular atresia while Cathepsin D‐dependent apoptosis may contribute to follicular cell apoptosis during late follicular atresia.